A new classification of injury patterns of the medial patellofemoral ligament after acute lateral patella dislocation detected using magnetic resonance imaging studies. Issue 2 (February 2019) - Cao, Hong; An, Qing; Gou, Bo; Ma, Shaocheng; Goh, En Lin; Xiong, Liang; Li, Yun guang; Ao, Feng
Abstract: Introduction: Acute lateral patellar dislocation is a very common condition in orthopedics, especially among adolescents and physically active patients. To evaluate distinct medial patellofemoral ligament (MPFL) injury patterns and the associated knee pathology after acute lateral patellar dislocation (ALPD) using magnetic resonance imaging (MRI) studies, which is essential for the development of treatment protocols. Materials and Methods: MRI images of 74 ALPD patients were taken between January 2015 to December 2016. Images were evaluated using standardized protocols. Results: The prevalence of MPFL injury following ALPD was 97.3% (72/74 patients). Among the 72 patients with MPFL, the prevalence of Type Ⅰ injury was 26.4% (19/72). Since only bone marrow edema and a partial tear were showed on MRI of these patients, conservative treatment was given. Tear of the MPFL occurred at the patellar attachment (Type Ⅱa) in 16 patients (16/72, 22.2%), at the middle area of the ligament (Type Ⅱb) in 5 patients (5/72, 6.9%), and at the femoral attachment (Type Ⅱc) in 27 patients (27/72, 37.5%). For Type Ⅱ injuries, all patients had the surgery to reconstruct the MPFL. The prevalence of Type Ⅲ MPFL injury was 6.9% (5/72) after the surgery. Conclusion: MPFL injury of is a common sequel following ALPD. We assessed the distinct injury pattern and associated pathology of MPFL using MRI studies. A good understanding of the injury pattern and associated knee pathology of MPFL is essential in managing patients with ALPD, especially if surgical intervention is considered.